DOI: 10.17077/etd.kt3jqulu
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nucleoside transporters and P-GP on the nasal uptake of Ribavirin

Abstract: Special thanks to my husband, Ibrahim Barjis, for his help and support during my studies, and to my beloved daughters, Larren, Seren, and Rose, thank you cheering me up in tough times, and drawing a smile on my face. Finally, I owe a special thanks to my family, my parents, my sister and best friend, my brothers and my sister in law for their love, encouragement, and prayers throughout my entire journey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Using NaviCyte Vertical Ussing Chambers, ribavirin permeation across the nasal olfactory mucosa was investigated in the presence of verapamil, a classic p-glycoprotein inhibitor. Bakri previously demonstrated that ribavirin showed concentration-dependent permeation across olfactory tissues [ 59 ], and when a 1.2 mg/mL ribavirin solution was tested, the drug permeability was found to be 1.3 × 10 −5 cm/s. However, when verapamil (50 µM) was included, the permeability of ribavirin increased nearly 2-fold to 2.6 × 10 −5 cm/s.…”
Section: Resultsmentioning
confidence: 99%
“…Using NaviCyte Vertical Ussing Chambers, ribavirin permeation across the nasal olfactory mucosa was investigated in the presence of verapamil, a classic p-glycoprotein inhibitor. Bakri previously demonstrated that ribavirin showed concentration-dependent permeation across olfactory tissues [ 59 ], and when a 1.2 mg/mL ribavirin solution was tested, the drug permeability was found to be 1.3 × 10 −5 cm/s. However, when verapamil (50 µM) was included, the permeability of ribavirin increased nearly 2-fold to 2.6 × 10 −5 cm/s.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, vain deeds are not worthy of being born of the Most Perfect God. 10 In the discourse of Islamic law, some figures who are representations of various theological ideologies such as the Asháriyah, Mu'tazilah, or Maturidiyah, basically do not disagree about the relation between`illah and maṣlahah as Maqāṣid al-shariah. The legal study of Maṣlahah in the context of Islamic law in the science of fiqh is prioritized to the value of legal benefits for humans.…”
Section: B the Concept Of Maqāṣid Al-shariahmentioning
confidence: 99%